Spillover effects of unconventional monetary policy on capital markets in the shadow of the Eurozone: A sample of non-Eurozone countries - Mercédesz Mészáros; Gábor Dávid Kiss (Review of Economic Perspectives, 2020)
The transmission mechanism has been dominated by direct monetary measures since the crisis of 2008. While the indirect impacts of the unconventional monetary instruments have not been fully explored yet. Monetary policy and funding conditions determine pricing sentiments for bond, stock and currency markets, represented by the volatilities of their main indicators: stock market indices, exchange rates, and yield premia. Our theoretical model takes spillover effects into account when it determines the variables which are responsible for volatility: the activities of international financial institutions (like the ESM or the IMF) are represented by dummy variables, while the limited autonomy in the shadow of the ECB is captured through gravity-like approaches. Six EU member states outside the Eurozone and Switzerland were analysed between 2007 and 2019 with random effect panel regression models to identify the differences in the impact of spillover effects on capital market volatilities. The results obtained are considered to be useful in mapping the potential effects of continuing monetary easing in the near future.
Keywords: C33; E43; E44; E52; E58; G15; 330; unconventional monetary policy; QE; spillover effects; capital markets